2018
DOI: 10.1136/bmjopen-2017-019422
|View full text |Cite
|
Sign up to set email alerts
|

Novel augmented reality solution for improving health literacy around antihypertensives in people living with type 2 diabetes mellitus: protocol of a technology evaluation study

Abstract: IntroductionLow health literacy is common in people with type 2 diabetes mellitus (T2DM) (up to 40%), associated with decreased self-efficacy in managing T2DM and its important complications, mainly hypertension. This study introduces, for the first time, an easy-to-use solution based on augmented reality (AR) on smartphones, to enhance health literacy around antihypertensive medicines. It assesses the feasibility of the solution for improving health literacy, oriented specifically to angiotensin II receptor b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…16 The participants of the present study also reported AR to be captivating and entertaining with a good impact on learning and brand recall and an overall positive experience in learning about hypertension. Previously, the literature has reported the utilization of digital technology and AR for enhancing disease-related education and nonpharmacological self-management strategies in hypertensive patients, 17,18 however, the authors could not find literature enhancing HCPs knowledge about hypertension using digital technology, AR, or VR.…”
Section: Discussionmentioning
confidence: 99%
“…16 The participants of the present study also reported AR to be captivating and entertaining with a good impact on learning and brand recall and an overall positive experience in learning about hypertension. Previously, the literature has reported the utilization of digital technology and AR for enhancing disease-related education and nonpharmacological self-management strategies in hypertensive patients, 17,18 however, the authors could not find literature enhancing HCPs knowledge about hypertension using digital technology, AR, or VR.…”
Section: Discussionmentioning
confidence: 99%
“…Digital health literacy is also used as a method of improving health literacy. One example is the use of Augmented Reality (AR) to improve health literacy about the use of antihypertensive medications in people with type-2 Diabetes Mellitus (T2DM) (Ahmadvand et al, 2018).…”
Section: Strategies To Improve Health Literacymentioning
confidence: 99%
“…Augmented reality is a 3D interactive form view of an actual physical environment that has been enhanced by adding digital information. 68 There are some ongoing studies 69,70 on using these technologies and evaluating their effectiveness in promoting HL. A successful example of using this technology was shown in a study by Jimenez et al, 71 where the virtual reality before radiotherapy for patients with breast cancer improved their understanding of the treatment.…”
Section: Strategy 6: Using Virtual Technologiesmentioning
confidence: 99%